Exploration and practice of data classification and grading based on DSMM - YUN Guigui; DU Bin; LIU Shumei (Tongxin xuebao)
Data assets have become one of the most important new assets and the most effective booster for digital transformation in universities. Its security issues are becoming increasingly prominent, and data classification and grading are the primary conditions for achieving data security management. Firstly, the two major challenges in data classification and grading were analyzed. Then, research conducted from the perspectives of institutional processes and technical tools based on the DSMM. With the practice of school data platforms, a data classification and grading protection system for schools was constructed, providing a solid guarantee for school data security management and sharing.